2020
DOI: 10.1111/edt.12626
|View full text |Cite
|
Sign up to set email alerts
|

Retromandibular transparotid approach for subcondylar mandibular fracture: A retrospective study

Abstract: Introduction The retromandibular transparotid approach provides the shortest and the most direct access to mandibular sub‐condylar fractures. However, this approach is less preferred due to the fear of facial nerve injury. The aim of this study was to evaluate the safety and morbidity of the retromandibular transparotid approach for open reduction and internal fixation of sub‐condylar mandibular fractures. Methods A retrospective cohort study of 29 patients with 35 sub‐condylar mandibular fractures who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 27 publications
(55 reference statements)
3
15
0
1
Order By: Relevance
“…Um outro ponto importante, consiste no fato de que lesões penetrantes na glândula parótida podem gerar sialoceles, as quais são definidas como coleção salivar em tecido subcutâneo 17 . A paciente apresentou tal condição no pós-operatório, que são consideradas complicações comuns não só em indivíduos acometidos por PAF na região, mas também naqueles tratadas por meio de acessos extraorais em região submandibular e retromandiular, por exemplo 19,20,21 . Seu diagnóstico pode ser feito por uma série de exames complementares, mas nesse caso o exame físico foi soberano em detrimento dos sinais que se tornavam mais evidentes durante as refeições.…”
Section: Discussionunclassified
“…Um outro ponto importante, consiste no fato de que lesões penetrantes na glândula parótida podem gerar sialoceles, as quais são definidas como coleção salivar em tecido subcutâneo 17 . A paciente apresentou tal condição no pós-operatório, que são consideradas complicações comuns não só em indivíduos acometidos por PAF na região, mas também naqueles tratadas por meio de acessos extraorais em região submandibular e retromandiular, por exemplo 19,20,21 . Seu diagnóstico pode ser feito por uma série de exames complementares, mas nesse caso o exame físico foi soberano em detrimento dos sinais que se tornavam mais evidentes durante as refeições.…”
Section: Discussionunclassified
“…As internal fixation errors are frequently reported when fixing the condyle to a single plate, a single 3D trapezoidal plate versus a single mini-plate is also highly recommended. In addition, when a single plate is used to repair a fractured condyle, the reduction of a mandibular symphysis fracture after condyle fixation may adversely affect the internal stabilization of the condyle [21][22] . In this review, the condylar fractures were immobilized with two mini plates along the stress line or with one 3D trapezoidal plate for good stabilization.…”
Section: Discussionmentioning
confidence: 99%
“…The most common was the RM transparotid (RMTP) approach, which was described in 7 studies. [11][12][13][14][15][16]18 MO Ten studies evaluated MO as a primary outcome. Göçmen et al 13 and Liu et al 15 reported an average MIO of 44.4 and 37.4 mm, respectively.…”
Section: Orif Approachesmentioning
confidence: 99%
“…Twelve studies evaluated postoperative outcomes after ORIF using a variety of surgical approaches as outlined in Table 3. The most common was the RM transparotid (RMTP) approach, which was described in 7 studies 11‐16,18 …”
Section: Orif Approachesmentioning
confidence: 99%
See 1 more Smart Citation